Smallholder farmers’ adaptation at the climate–conflict nexus: a systematic review - Rubangakene, Damasco; Oryema, Christine; Nielsen, Martin Reinhardt (Frontiers in Climate, 2026)
In conflict-affected settings, smallholder farmers’ adaptation is complex due to the interconnected nature of social, environmental, and economic vulnerabilities. While many studies have systematically reviewed the causal pathways between conflict and climate, less attention has been given to synthesizing evidence on how smallholder farmers adapt to climate change and contextual vulnerabilities in these settings. Knowledge on adaptation at the climate–conflict nexus remains scattered across disciplines, highlighting the need for a systematic review to consolidate evidence and inform resilience-building strategies. This study aimed to systematically review empirical literature on smallholder farmers’ adaptation to climate change in conflict-affected areas, providing an integrated understanding of adaptation strategies at the climate–conflict nexus. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, a one-time search of scholarly literature was conducted on November 29, 2024, using the terms “climate change,” “conflict,” “adaptation,” and “smallholder farmers” and their synonyms, across three databases: Web of Science Core Collection, Scopus, and ProQuest. Eligible studies were peer-reviewed, empirical, published in English between 2004 and 2024, and focused on how smallholder farmers respond to climate change in conflict contexts. Theoretical studies, non-peer-reviewed work, or studies that did not address both conflict and climate change or did not focus on smallholder farmers were excluded. A hybrid approach was used to extract and synthesize data from the selected studies. Most studies were concentrated in the Global South, with growing attention from 2016 to 2024, reflecting increased awareness of the climate–conflict nexus. The review identified eleven integrated strategies for addressing interwoven vulnerabilities in conflict-affected settings. However, 67% of studies did not link adaptive capacities to specific vulnerabilities, and one-third did not consider how adaptation is shaped by power relations within social hierarchies. These findings underscore the need for further research on socially stratified adaptation in conflict-affected contexts and highlight the importance of context-specific policies for smallholder farmers. By consolidating fragmented evidence, this review provides guidance for development agencies, local governments, and NGOs in designing integrated climate–conflict interventions that strengthen resilience, reduce vulnerability, and promote sustainable livelihoods.